The Influence of Public Employee Trust on Organizational Commitment in Jinan, China: The Mediating Roles of Burnout - Junlin Shang; Janifer Anak Lunyai; Norizan Jaafar (Business Management and Strategy, 2026)
This study investigates the influence of public employee trust on organizational commitment in Jinan, China, with a particular focus on the mediating role of burnout. A total of 204 public employees participated in the research, selected through purposive sampling. Using a quantitative research design, the study empirically confirmed that public employee trust has a significant positive impact on organizational commitment. Moreover, burnout was found to partially mediate this relationship, indicating that while higher trust directly enhances organizational commitment, it also reduces burnout, which in turn strengthens employees’ commitment. Despite these contributions, the study is limited by its single-city sample, cross-sectional design, and reliance on self-reported data. Future research should employ larger and more diverse samples, longitudinal designs, and additional mediators or moderators to provide a more comprehensive understanding of how trust shapes commitment in the public sector. The findings have important implications, suggesting that building trustful work environments and reducing burnout can enhance employee commitment, while policymakers and administrators should adopt strategies that foster trust and promote employee well-being to strengthen organizational performance.